Tekoälyavusteinen ohjelmistokehitys: Generatiivisen tekoälyn lisäarvo ja käytön haasteet - Nurminen, Jami (2025)
This master's thesis examines the role of Generative Artificial Intelligence in the context of software development and presents its key benefits and challenges. The theoretical part of research covers the evolutionary path of artificial intelligence from the 1950s to the pre-sent day, focusing on the innovations that enabled the emergence of generative artificial intelligence. This master´s thesis also addresses the key factors affecting software devel-opment efficiency and presents several frameworks, of which the SPACE framework was identified as most relevant. The empirical section is based on qualitative thematic inter-views with six software development professionals from the case company CGI. The data were analyzed using an abductive approach in which the SPACE framework played a prominent role. The study suggests that tools based on generative artificial intelligence can improve development efficiency through automation of routine tasks, enhanced learning, increased confidence, and minimized interruptions to the flow state. On the other hand, the study highlights the limitations of artificial intelligence in terms of technological challeng-es and risks of use. The use of artificial intelligence can lead to a loss of critical thinking when artificial intelligence responses are used without validation of AI-generated outputs. The results highlight the impact of generative artificial intelligence on the efficiency of software development and provide organizations with a comprehensive view of the bene-fits of different AI tools and the factors contributing to an AI-friendly environment.